Tramas de Afrodite e Eros: sedução e capitulação na mélica grega arcaica (Nuntius Antiquus, 2011)
This article presents a study of Aphrodite’s and Eros’s images in archaic Greek melic poetry, in some fragments where the “I”, as a result of their divine action, becomes a helpless victim of the power of erotic desire and/or a seducer/seductress in pursuit of the beloved one. These are the melic poets and fragments herein commented: Alcman (Fr. 59(a) Dav.), Sappho (Frs. 1, 102 Voigt), Ibycus (Frs. 286, 288, 287 Dav.).